Review of Mycetobia Meigen, 1818 (Diptera, Anisopodidae) in the Eocene ambers - Wojtoń, Maciej; Kania, Iwona; Krzemiński, Wiesław (Zootaxa, 2019)
A revision of the genus Mycetobia Meigen, 1818 from the Eocene is presented. Redescription of Mycetobia connexa Meunier, 1899 known from the Baltic amber is given and documented by photographs and drawings. Five new species of Mycetobia from Eocene resins are described, four from Baltic amber: Mycetobia christelae sp. nov., Mycetobia hansi sp. nov., Mycetobia silvia sp. nov., Mycetobia szwedoi sp. nov. and one from the Ukrainian amber: Mycetobia perkovskyi sp. nov. Key to the species of Mycetobia known from the Eocene is provided.